Regulación para lograr los objetivos públicos: el caso de los servicios públicos de Colombia - Moreno, Luis Ferney (2016)
Since the 1990s, several countries in Latin America liberalized and privatized the public utilities business. As a consequence, there was a transit from the Entrepreneur State to the Regulatory State, the latter being traditionally understood as a model of regulation for competition, with a mayor concern only on economic objectives. Notwithstanding, the socioeconomic reality of Latin American countries, in particular Colombia, presented the fact that competition cannot be the only priority, and that regulation of the public utilities business must also achieve social objectives. Public purposes, understood as economic and social objectives, are the cornerstone of State intervention.